2015
DOI: 10.1080/15287394.2015.1072070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Safety ofArrabidaea chicaVerlot (Bignoniaceae), a Plant with Healing Properties

Abstract: Arrabidaea chica Verlot (Bignoniaceae) has been used as a medicinal herb to treat anemia, hemorrhage, inflammation, intestinal colic, hepatitis, and skin infections in the Brazilian Amazon region. Studies have demonstrated the healing properties of extracts obtained from A. chica leaves, which contain anthocyanins and flavonoids. However, few investigations have assessed the safe use of this plant species. In this study, mutagenic and genotoxic effects of a crude aqueous extract, a butanolic fraction, and aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…A previous study [52] also demonstrated the efficiency of A. chica in the treatment of anemia, inflammation, intestinal colic, hepatitis, and skin infections. The research group evaluated the crude aqueous extract and the fractions of Arrabidaea in Salmonella tests to investigate the mutagenic potential of the chemical compounds in A. chica.…”
Section: Main Chemical Composition Of a Chicamentioning
confidence: 82%
“…A previous study [52] also demonstrated the efficiency of A. chica in the treatment of anemia, inflammation, intestinal colic, hepatitis, and skin infections. The research group evaluated the crude aqueous extract and the fractions of Arrabidaea in Salmonella tests to investigate the mutagenic potential of the chemical compounds in A. chica.…”
Section: Main Chemical Composition Of a Chicamentioning
confidence: 82%
“…According to the literature, pharmacological studies have demonstrated cytotoxic and leishmanicidal potential (Cortez de S a et al, 2016), anti-T. cruzi (Barbosa et al, 2008), anti-inflammatory, antiangiogenic and antiproliferative activities (Michel et al, 2015), antimicrobial activity (Mafioleti et al, 2013) and significant antioxidant activity (Siraichi et al, 2013). Previous phytochemical studies of this plant have shown the presence of tannins, flavonoids (7,4 0 -dihydroxy-5methoxyflavone, luteolin, carajuruflavone, apigenin, escutelarina and isoescutelarina), phytosterols, anthocyanidins and pigments used in cosmetics like carajurone and carajurin (Zorn et al, 2001; Barbosa et al, 2008;Gemelli et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…The isolated compound [1] was also non-cytotoxic, with IC 50 > 400 µg/mL for CHO-k1 and 387.00 ± 4.06 µg/mL for RAW 264.7. These results complement previous works indicating than HEFc does not cause any signs of acute toxicity in mice when administered in vivo at doses up to 3 g/kg p.o., and the absence of mutagenic or genotoxic risks (Mafioleti et al 2013;Gemelli et al 2015).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%